Antenatal Betamethasone Every 12 Hours in Imminent Preterm Labour - Saldaña-García, Natalia; Espinosa Fernández, María de Gracia; Martínez Pajares, José David; Tapia-Moreno, Elías; Moreno-Samos, María; Cuenca-Marín, Celia; Ríus-Díaz, Francisca; Sánchez-Tamayo, Tomás (My University, 2022)
Background: Benefits of antenatal corticosteroids have been established for preterm infants who have received the full course. In imminent preterm labours there is no time to administer the second dose 24 h later. Objective: To determine whether the administration of two doses of betamethasone in a 12 h interval is equivalent to the effects of a full maturation. Methods: We performed a retrospective cohort study including preterm infants ≤34 weeks gestational age at birth and ≤1500 g, admitted to an NICU IIIC level in a tertiary hospital from 2015 to 2020. The population was divided into two cohorts: complete maturation (CM) (two doses of betamethasone 24 h apart), or advanced maturation (AM) (two doses of betamethasone 12 h apart). The primary outcomes were mortality or survival with severe morbidities. The presence of respiratory distress syndrome and other morbidities of prematurity were determined. These variables were analysed in the neonates under 28 weeks gestational age cohort. Neurodevelopment at 2 years was evaluated with the validated Ages and Stages Questionnaires®, Third Edition (ASQ®-3). Multiple regression analyses were performed and adjusted for confounding factors. Results: A total of 275 preterm neonates were included. Serious outcomes did not show differences between cohorts, no increased incidence of morbidity was found in AM. A lower percentage of hypotension during the first week (p = 0.04), a tendency towards lower maximum FiO2 (p = 0.14) and to a shorter mechanical ventilation time (p = 0.14) were observed for the AM cohort. Similar results were found in the subgroup of neonates under 28 weeks gestational age. There were no differences in cerebral palsy or sensory deficits at 24 months of corrected age, although the AM cohort showed a trend towards better scores on the ASQ3 scale. Conclusions: Administration of betamethasone every 12 h showed similar results to the traditional pattern with respect to mortality and severe morbidities. (...)
Keywords: Antenatal corticosteroids; Betamethasone; Preterm infant; Mortality; Respiratory distress syndrome; Neurodevelopmental